Political parties and leaders of the New Right at Bolsonaro’s Brazil - Goldstein, Ariel (2021)
This paper analyzes the political reorganization of the right wing in the Brazilian Congress. The background of the main leaders, history and ideologicalpositions of the most relevant parties are considered. The Social Liberal Party (PSL), the New Party (PN), the Brazilian Social Democracy Party(PSDB) and the Democrats (DEM) are considered. By succinctly analyzing the trajectory of these political parties and their leaders, it will be possibleto better understand the agenda and the type of relationship between the Executive and the Legislative Chambers during the Bolsonaro administration.The change represented by the arrival of this former Army captain to the presidency of Brazil, meant a modification in the political identities of the main right-wing parties. However, the article argues that the arrival of Bolsonaro to the presidency and his new alliances in Congress should not be interpreted as an attempt to put an end to the so-called “coalition presidentialism”, but rather as a reorganization of it.